Futsal booking web based system integrate with telegram notifications / Nur Izzat Hakim Norazam and Mohd Nizam Osman - Norazam, Nur Izzat Hakim; Osman, Mohd Nizam (College of Computing, Informatics and Media, UiTM Perlis, 2023)
In Malaysia, most of the court futsal facilities are still dependent on paper-based record system. Futsal booking web based system integrate with telegram notification is a web application to assist customer and futsal court staff in managing futsal court booking. Following a visit or attend at futsal court, this system will document customers’ information such as name, no phone, and telegram chat id. Customers also has ubiquitous access to their booking record within the web app. Besides, telegram notifications is use by the admin to sent booking details by telegram chat bot. User Acceptance Testing (UAT) with 31 respondents was conducted to validate the prototype. The respondents include customers, court futsal staff, student who always plays futsal. Results from the UAT shows that the prototype obtained constructive feedback from users. Therefore, it can be concluded that the objective for this study is successfully attained.